The Challenges That Faced Teachers and Students' Communication During COVID 19 At The Faculty of Human Science - Bani, Fatima Omar; Bani, Khawla Salem; Alneari, Marwa Ahmed; Salem, Mona M. M. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The COVID-19 epidemic affected individuals from all walks of life, as they were instructed to self-quarantine in their houses to prevent the virus from spreading. The lockdown has major consequences for mental health, resulting in psychological issues such as frustration, stress, and sadness. With the closure of educational institutions, the need for a rapid transition from traditional learning to the digital sphere of learning emerged. Online learning has been observed as a possible alternative to conventional learning. This research discusses the concept of evaluating university teaching, the perceptions of lecturers about evaluating universities, and its effects on higher education teaching and learning processes. A survey study was conducted on a group of lecturers from the Faculty of Human Sciences at Alasmarya University in Libya. This data was collected from English language students by using a questionnaire and interviews with teachers, and then it was analysed. As a result of the findings, the researchers recommended improving the teaching process from offline to online learning and found that the research has achieved what it aims to do by affecting students' learning for more than two years.
Keywords: COVID-19 epidemic; Online learning; Evaluation; Teaching process